1994
DOI: 10.1016/s0006-3495(94)80554-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser imaging of rapid Ca2+ gradients in excitable cells

Abstract: Excitable cells are thought to respond to action potentials by forming short lived and highly localized Ca2+ gradients near sites of Ca2+ entry or near the site of Ca2+ release by intracellular stores. However, conventional imaging techniques lack the spatial and temporal resolution to capture these gradients. Here we demonstrate the use of pulsed-laser microscopy to measure Ca2+ gradients with submicron spatial resolution and millisecond time resolution in two preparations where the Ca2+ signal is thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 40 publications
5
65
1
1
Order By: Relevance
“…Although chromaffin cells do not form synapses onto other cells, secretion from individual cells may be polarized in the direction of blood vessels (24,26), for example, by restricting the zones of Ca2+ entry. Indeed, in chromaffin cells Ca2+ channels appear to be clustered (30). Such clustering apparently results in "hot spots" of secretion, as has been reported by Schroeder et al (24), using carbon-fiber electrodes having tip diameters of about 2 ,um.…”
mentioning
confidence: 52%
“…Although chromaffin cells do not form synapses onto other cells, secretion from individual cells may be polarized in the direction of blood vessels (24,26), for example, by restricting the zones of Ca2+ entry. Indeed, in chromaffin cells Ca2+ channels appear to be clustered (30). Such clustering apparently results in "hot spots" of secretion, as has been reported by Schroeder et al (24), using carbon-fiber electrodes having tip diameters of about 2 ,um.…”
mentioning
confidence: 52%
“…1A) that continues even after the presynaptic neuron has been repolarized (15,17) while the intracellular Ca2+ concentration is thought to remain high. As measured in chromaffin cells (19) J r(t')Im(t -t')dt'. [1] Minis were usually elicited by partial activation of the presynaptic Ca2+ current through depolarizations to approximately -35 mV, so that quanta were discretely resolvable (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the possible cause of such heterogeneity is through the Ca 2+ hotspots that are generated in the membrane (Monck et al, 1994) or even through Ca 2+ release from intracellular reservoirs, such as mitochondria (Pozzan and Rizzuto, 2000;Montero et al, 2002) or the endoplasmic reticulum (ER) . One simple explanation for this heterogeneity is the organization of the cytosolic space itself, which is structured as a dense intricate network of dynamic cytoskeletal polygonal cages that can be readily studied in live cells by transmitted-light microscopy (Giner et al, 2005;Giner et al, 2007).…”
Section: Cytoskeletal Organization and The Distribution Of Fluorescenmentioning
confidence: 99%